Advances in Chemical Composition, Extraction Techniques, Analytical Methods, and Biological Activity of Astragali Radix - Chang, Xiangna; Chen, Xuefeng; Guo, Yuxi; Gong, Pin; Pei, Shuya; Wang, Danni; Wang, Peipei; Wang, Mengrao; Chen, Fuxin (Molecules (Basel, Switzerland), 2022)
Astragali Radix (AR) is one of the well-known traditional Chinese medicines with a long history of medical use and a wide range of clinical applications. AR contains a variety of chemical constituents which can be classified into the following categories: polysaccharides, saponins, flavonoids, amino acids, and trace elements. There are several techniques to extract these constituents, of which microwave-assisted, enzymatic, aqueous, ultrasonic and reflux extraction are the most used. Several methods such as spectroscopy, capillary electrophoresis and various chromatographic methods have been developed to identify and analyze AR. Meanwhile, this paper also summarizes the biological activities of AR, such as anti-inflammatory, antioxidant, antitumor and antiviral activities. It is expected to provide theoretical support for the better development and utilization of AR.